Kubo and the two strings - Knight, Travis, 1973-; Theron, Charlize; Parkinson, Art; McConaughey, Matthew, 1969-; Marianelli, Dario (Universal City, CA : Universal Pictures Home Entertainment, 2016)
When a spirit from the past wreaks havoc on Kubo's life, he must locate a magical suit of armor that was once worn by his late father, a legendary samurai warrior.
Originally released as a motion picture in 2016.
Dolby digital 5.1, anamorphic wide screen 2.40:1.
Features: Corners of the Earth, feature commentary with Travis Knight, and more.
Director of photography, Frank Passingham ; production designer, Nelson Lowry ; editor, Christopher Murrie ; music, Dario Marianelli.
Voices: Charlize Theron, Art Parkinson, Matthew McConaughey, Ralph Fiennes, George Takei.
MPAA rating: PG.
Keywords: Samurai -- Drama; Fathers and sons -- Drama; Spirits -- Drama; Action and adventure films; Stop-motion animation films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Fantasy films; Animated films